Crystallographic analysis, transport features and magnetic properties of the Ca La Ba Cu 3-x Gax O7-d superconducting material - C.A. Parra Vargas (Revista Mexicana de Física, 2007)
Results of structure, superconductivity and normal state magnetism of the CaLaBaCu3°xGaxO7°±superconductor are presented. A struc-tural study was performed by powder X-ray diffraction and magnetic characterization by SQUID (Superconducting Quantum InterfaceDevice) magnetometer. Electrical resistivity measurements were performed by using a low-frequency AC-technique. The transition tem-perature (Tc) of the pristine sample decreases with an increase in the doped Ga concentration. The main cause of the decrease inTcis theeating of holes due to the Cu2+/Ga3+alliovalent substitution, along with the disorder created due to the ionic size mismatch between Ga andCu-ions. In the normal state, the molar susceptibility for several samples fit to the Curie-Weiss law, which permitted the obtainment of thecorresponding magnetic parameters,e.g., the effective magnetic moment, the Curie temperature and the temperature independent term.- . .